(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores the legal regulation of personal insolvency in the Republic of Uzbekistan, focusing on the recently enacted Law on Insolvency (2022). Drawing on international best practices and comparative analyses, it evaluates the socio-economic causes of insolvency, such as economic shocks, life events, and credit mismanagement, and highlights preventive measures, including financial literacy programs, debt counseling, and strengthened social safety nets. By analyzing global frameworks, such as those of France and the UK, and the principles outlined by UNCITRAL, the study underscores the importance of tailored approaches to balancing creditor-debtor dynamics and protecting essential assets. The findings suggest that Uzbekistan’s reforms align with international standards but require further enhancements to address administrative delays, informal debt structures, and rehabilitation mechanisms. This comprehensive evaluation contributes to the understanding of personal insolvency and offers actionable insights for policymakers to foster economic resilience and reduce over-indebtedness.